2015
DOI: 10.1073/pnas.1510435112
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for superconductivity in Li-decorated monolayer graphene

Abstract: Monolayer graphene exhibits many spectacular electronic properties, with superconductivity being arguably the most notable exception. It was theoretically proposed that superconductivity might be induced by enhancing the electron-phonon coupling through the decoration of graphene with an alkali adatom superlattice [Profeta G, Calandra M, Mauri F (2012) Nat Phys 8(2):131-134]. Although experiments have shown an adatom-induced enhancement of the electron-phonon coupling, superconductivity has never been observed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
265
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(294 citation statements)
references
References 38 publications
24
265
3
Order By: Relevance
“…While previous ab initio calculations have shown that the electron-phonon coupling is sufficient to yield a critical temperature in 6.7-10.3 K range using the Allen-Dynes formula [3,13,14] or the isotropic Eliashberg formalism [15], the nature of the superconducting gap has not yet been addressed. We find that, similar to bulk CaC 6 [15][16][17][18], Li-decorated monolayer graphene exhibits a single anisotropic gap in agreement with the experimental work [8].…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…While previous ab initio calculations have shown that the electron-phonon coupling is sufficient to yield a critical temperature in 6.7-10.3 K range using the Allen-Dynes formula [3,13,14] or the isotropic Eliashberg formalism [15], the nature of the superconducting gap has not yet been addressed. We find that, similar to bulk CaC 6 [15][16][17][18], Li-decorated monolayer graphene exhibits a single anisotropic gap in agreement with the experimental work [8].…”
Section: Introductionsupporting
confidence: 87%
“…4(a) we find T c = 5.9 K and a ratio 2∆ 0 /k B T c = 3.50, very close to the ideal BCS value of 3.53 [44]. The predicted superconducting critical temperature is in excellent agreement with the experimental estimation of 5.9 K based on measurements of the size of the superconducting gap [8]. The temperature dependence of the superconducting gap can be well fitted with a BCS model, as obtained by solving numerically the BCS gap equation [45] with ∆ 0 and T c from our first-principles calculations.…”
Section: Superconducting Propertiessupporting
confidence: 82%
See 1 more Smart Citation
“…In June, physicists in the United States and South Korea reported "the world's thinnest light bulb," using light-emitting graphene as an ultrathin filament (15). And in September, an international team of researchers reported that, at low temperatures, the material becomes a superconductor when coated with lithium (16).…”
Section: Ubiquitous Electronicsmentioning
confidence: 99%
“…Furthermore, additional experimental progress has been made regarding evidence of superconductivity in Li-decorated monolayer graphene with a transition temperature of approximately 5.9 K [15].…”
Section: Introductionmentioning
confidence: 99%